Potential Biomarkers as Early Detection of Diabetic Cardiomyopathy - Hariadi Hariadi; Maia Thalia Giani; Silvia Handika Anggraeni (Universitas Airlangga, 2021)
Diabetes mellitus (DM) is one of the most prevalent and burdensome among chronic disease worldwide. Its complications accelerate mortality rate within population. Diabetic cardiomyopathy (DCM) is one of diabetes macrovascular complications, which symptoms are frequently unforeseen. Advances in pathogenesis understanding DCM underlying mechanisms remain not fully perceived. Current diagnostic approach of DCM can hardly determine diabetic patients with asymptomatic cardiomyopathy. Previous studies suggested biomarkers might detect early stage DCM. There are numerous selective biomarkers representing several pathophysiological pathways, such as myocardial fibrosis, inflammatory response, cardiomyocyte apoptosis, and metabolic dysregulation in the development of diabetic heart anomaly It was also reported those biomarkers are useful for the prognostic assessment of the disease. However, not all biomarkers are cardiac specific and can be an auspicious diagnostic tool candidate. Recent studies show that there are certain biomarkers, such as microRNA, H-FABP, IGFBP7, and some other novel cardiac biomarkers were more specifically associated with the pathological mechanism of DCM. In this review, we aimed to discuss the role of several potential cardiac biomarkers as early detection in DCM that may predict future incident of DCM, and contribute to improving mortality prediction in patients with subclinical DCM. Keywords: Biomarker, Cardiomyocyte, Diabetic Cardiomyopathy, Diastolic